2018
DOI: 10.1021/acsami.8b07298
|View full text |Cite
|
Sign up to set email alerts
|

Bias-Dependent Normal and Inverted JV Hysteresis in Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) typically exhibit hysteresis in current density-voltage ( J- V) measurements. The most common type of J- V hysteresis in PSCs is normal hysteresis, in which the performance in the reverse scan is better than that in the forward scan. However, inverted hysteresis also exists, in which the reverse scan performance is worse than in the forward scan; this hysteresis, however, is significantly less well studied. In this work, we show that the hysteresis decreases when the sweep rate is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 48 publications
2
70
0
Order By: Relevance
“…[42] A two-dimensional laminate (SiÀ C) can have a thickness of~20 nm (~20 layers of silicene), which allows you to maintain flexibility and retain the capacity of the multilayer anode design as was in the case of an amorphous silicon film of the same thickness. [43] A sandwich structure for silicene anode can be proposed: separator (polypropylene, PP)/LiPON/Silicene + graphene/Al. The thickness of the LiPON layer can be about 50 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[42] A two-dimensional laminate (SiÀ C) can have a thickness of~20 nm (~20 layers of silicene), which allows you to maintain flexibility and retain the capacity of the multilayer anode design as was in the case of an amorphous silicon film of the same thickness. [43] A sandwich structure for silicene anode can be proposed: separator (polypropylene, PP)/LiPON/Silicene + graphene/Al. The thickness of the LiPON layer can be about 50 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have clearly shown that mobile ions related to ionic vacancies/interstitial defects and negatively/positively charged ions in PSCs can migrate with a small external electric field, which is more activated under illumination. [20,47,48] Figure 9 shows the schematic band diagrams with ions displaced by an electric field and diffusion in PSCs. The differences in the Fermi level between the charge-selective layers force the mobile ions to be driven by a built-in voltage to each counter electrode in the electrical contact under the dark condition until the internal electric field is screened by the ion distribution to establish an equilibrium state.…”
Section: Investigation Of Charge Transfer Using Electrochemical Impedmentioning
confidence: 99%
“…6a). 48 But also negatively charged ions or vacancies can act as recombination centres (right side in Fig. 6a) 37,48,49 that essentially inhibit any charge carrier to be injected into the respective transport layers and can therefore not be measured externally by an electrical measurement.…”
Section: Relationship Between the Evolution Of R And Cmentioning
confidence: 99%
“…48 But also negatively charged ions or vacancies can act as recombination centres (right side in Fig. 6a) 37,48,49 that essentially inhibit any charge carrier to be injected into the respective transport layers and can therefore not be measured externally by an electrical measurement. The major part of the perovskite absorber might still be active in creating charge carriers, but this activity is screened by the recombination centres and the behaviour of the whole device mimics a smaller device.…”
Section: Relationship Between the Evolution Of R And Cmentioning
confidence: 99%